Shamanic elements in the poetry of Ted Hughes - Panecka, Ewa (Cambridge Scholars Publishing, 2018)
Shamanism is not a religion, but a technique of achieving ecstasy through chanting, the beating of a drum and the shaking of a rattle, all with the aim of communing with the spirits and rescue afflicted souls. If poetry is a healing substance, poets are shamans of words, who journey into the magic land of art in order to bring the energy and imagery of dreams into physical reality. Shamans, the poets of consciousness, can heal the soul and thus lead the reader to spiritual rebirth and moral regeneration. The book interprets the poetry of Ted Hughes as a product of shamanic performance, the work.